Prevalence and associated factors of anaemia among pregnant women in a rural area of Bangladesh - Hyder, S.M. Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
This study describes the anaemia prevalence and associated factors among pregnant women in a rural community in Bangladesh. The study women were recruited from 50 BRAC antenatal care centres. A total of 216 pregnant women during second trimester of pregnancy were included from rural communities of Mymensingh during May to November 1997. Information was collected on demographic and socioeconomic factors, reproductive history, last menstrual period, fundal height, mid upper arm circumference, haemoglobin concentration as well as ascaris and hookworm infestations. The result indicates that 56% of the pregnant women were found anaemic according to the WHO criteria. There was no case of severe anaemia and the prevalence of mild and moderate anaemia was 22.7'% and 32.9% respectively. Women 's age, household landholding and occupation categorised as farming and nonfarming were significantly associated with the anaemia prevalence (p~O . OS) . Malnourished women in farming households had higher anaemia prevalence. However, nutritional status was not associated with anaemia prevalence among women in non-farming households (p>O.OS) Anaemia seems to have very high prevalence among pregnant women irrespective of their parity and socioeconomic status. Further studies are required to investigate the causes of anaemia during pregnancy.